ASSESSING THE PREVALENCE OF AHIMA-IDENTIFIED HEALTH INFORMATICS AND INFORMATION MANAGEMENT CAREERS AND RELATED SKILLS: A CROSS-SECTIONAL STUDY. - Madlock-Brown, Charisse R.; Sharp, Marcia Y.; Reynolds, Rebecca B. (Perspectives in Health Information Management)
This study's objective was to identify the prevalence of the American Health Information Management Association (AHIMA) career map jobs and determine which job categories, degrees, and skills are associated with higher pay. We extracted data from SimplyHired, a major employment website, from December 2018 to December 2019. We retrieved 12,688 career posts. We found differences in average salary by career category (p-value 0.00). Most jobs were in coding and revenue cycle (CRC) and information governance (IG) categories. The highest average salaries were in data analytics (DA) and informatics (IN). Each career category had a unique set of skills associated with the highest paying jobs. Eighty-two percent of CRC, 67 percent of IG, 65 percent of IN, and 83 percent of DA jobs listed in the AHIMA career map were present in the extracted dataset. These results can help employees, academics, and industry leaders understand the health informatics and information management (HIM) workforce landscape.